(untitled) - Rue, Leslie W.; Leslie W. Rue (Mission Hills, Calif., 1994)
Business Management: Real-World Applications and Connections gives students an understanding of the way business works. It develops their technical knowledge and competence. Classroom experience is enhanced through a blend of text, visual presentation, and interactive resources
Keywords: Small business; Entrepreneurship